The Primary Works of Urdu Linguistics, A Research based critical analysis - Dr. Sajid Javed (Zaban-o-Adab, 2022)
The Tradition of Urdu Historical and Descriptive Linguistics has not a wide historical traces. As the educational discipline, the situation of the scientific study of this language is not satisfactory in Pakistan. The primary sources of this discipline can be searched in the 17th century of sub-continent. The scattered work was not a serious effort in this way. John Gilchrist Came to Bombay in 1782, and devise a plan to establish the Urdu linguistics works in a scientific manner. He wrote more than 20 titles for Urdu Linguistics and set a serious ground in the field of 2nd Language Acquisition, Language Pedagogy, Historical Linguistics, Grammar and Dictionary writing and dialogues of Urdu and English languages for Colonial purposes. This article shows a critical and research analysis of Urdu Linguistics Traces in early history.